Bullwhip Effect in Logistics: Bibliometric Analysis and Multi-Criteria Decision-Making Approaches - Amelia Ghania; Tatang Permana; Hanissa Okitasari (Fakultas Teknik Universitas Muria Kudus, 2026)
Supply chains and logistics support global economy activity, where disruptions can occur in the form of demand fluctuations across multi-echelon systems, known as the bullwhip effect. Research objectives focus on analysis publications development of bullwhip effect 2020–2025 period, identifying causal factors, mitigation strategies, and determining priority mitigation recommendations. An integrated research approach is implemented through a Systematic Literature Review, bibliometric analysis, and the Fuzzy Analytical Hierarchy Process (F-AHP). Literature selection is conducted using Scopus, Taylor and Francis, Lens, OpenAlex, Dimensions AI, and Google Scholar databases. Initial identification yields 1,081 publications, from which 494 articles are selected based on defined inclusion and exclusion criteria. Bibliometric analysis is performed using RStudio and VOSviewer to examine publication trends, citation patterns, geographical distribution, and thematic structures. Expert evaluations are processed using F-AHP to prioritize mitigation strategies. Results of the literature synthesis identify five dominant bullwhip effect causal factors, including supply chain structure & policy, demand uncertainty & variability, information & ordering distortion, operational & managerial decision-making, and supply & distribution disruptions. Expert assessment identifies Policy and Coordination as the highest priority strategy, with Inventory Management, Centralization, and Decentralization as the main recommended strategy mitigation, afterward Information Sharing with Vendor Managed Inventory (VMI), Operational Strategy with Demand Forecasting, and Technology and Innovation with Digitalization. Contributions to knowledge support researchers and practitioners in strengthening supply chain resilience and sustainability also provide guidance for future research.